الدور التربوي للوالدين في التنشئة الاجتماعية للطفل المعاق إعاقة جسدية - بوراس, كاهينة (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة الحالية إلى التعرف على دور الوالدين لتنشئة الطفل الذي يعاني من إعاقة جسدية (حركية أو بصرية)، حيث بلغت عينة البحث (25) طفلا معاقا إعاقة جسدية، في كل من المركز البيداغوجي لولاية البويرة والمركز رعاية المكفوفين ببوخالفة بولاية تيزي وزو، حيث تم الاعتماد على المنهج الوصفي، وقد تم استعمال استبيان من إعداد الباحثة لتعرف على دور الوالدين في التنشئة الإجتماعية للطفل المعاق، مكون من (50) عبارة موزعة على خمسة أبعاد. وتوصلت الدراسة إلى نتائج مرتفعة في بعدي العلاقات الأسرية والتنشئة الاجتماعية لإستبيان وبالتالي يظهر أن للوالدين دور كبير في التنشئة الاجتماعية للطفل المعاق إعاقة حركية. . Abstract: The current study aimed to identify the role of parents in raising a child with a physical (motor or visual) handicap. the sample is made up of (25) disabled children at the educational center of the wilaya of BOUIRA and the center for the blind of Boukhalfa. Relying on the descriptive approach, a questionnaire prepared by the researcher was used to identify the role of parents in the socializatio of the disabled child, consisting of (50) syntaxes distributed over five categories. The study reached high results in the two dimensions of family relations and socialization of a questionnaire, and thus it appears that parents have a major role in the socialization of a handicapped child with a motor disability. Keywords: role; handicap; socialization; family role.
The educational role of parents in the socialization of a physically handicapped child
مقال
Keywords: دور، إعاقة، تنشئة اجتماعية، دور الأسرة; role , handicap, socialization, family role